2001
DOI: 10.1046/j.1469-0705.2001.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of fetal hydronephrosis diagnosed on mid‐trimester ultrasound

Abstract: The current study highlights the natural history of antenatally detected hydronephrosis. Mild fetal hydronephrosis appears to be associated with an excellent prognosis and probably represents the group with physiological renal pelvic dilatation. Moderate/severe fetal hydronephrosis is associated with poorer outcome and is perhaps the group that will need more intense follow up both antenatally and postnatally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
1
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(147 citation statements)
references
References 18 publications
10
124
1
7
Order By: Relevance
“…Alternatively, urinary tract dilatation might occur normally during urinary tract development, perhaps due to the occurrence of VUR before the formation of a competent flap-valve mechanism. In reviewing the long-term follow-up of antenatal urinary tract dilatation, there are always some cases where previously observed abnormalities are no longer detected in the postnatal period (14,25). Our data suggest that in wild-type mice, VUR resolves in the newborn period because the flap-valve mechanism has now become competent.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Alternatively, urinary tract dilatation might occur normally during urinary tract development, perhaps due to the occurrence of VUR before the formation of a competent flap-valve mechanism. In reviewing the long-term follow-up of antenatal urinary tract dilatation, there are always some cases where previously observed abnormalities are no longer detected in the postnatal period (14,25). Our data suggest that in wild-type mice, VUR resolves in the newborn period because the flap-valve mechanism has now become competent.…”
Section: Discussionmentioning
confidence: 81%
“…Urinary tract dilatation discovered on antenatal ultrasounds is not always detected on postnatal imaging (14,25). This raises many questions regarding its natural history, including the possibility that dilatation can occur as a transient finding during normal human embryogenesis (20).…”
Section: Hoxb7/ret Mice Have a High Incidence Of Vur Hoxb7/retmentioning
confidence: 99%
“…Five hundred and six potentially relevant studies were identified, of which 18 met the inclusion criteria (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Two studies reported overlapping patient cohorts but different outcomes (27,28).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We undertook a systematic review and metaregression analysis of cohort studies that reported outcomes of fetal RPD, for fetuses with an RPD of Յ15 mm. The primary analyses were based on fetuses identified by routine fetal ultrasound screening (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Secondary analyses evaluated studies that included pregnancies referred for specialist obstetric/fetal medicine reasons (29 -34).…”
Section: To Screen or Not To Screen That Is The Question: Whether 'mentioning
confidence: 99%
“…The estimated incidence of antenatal hydronephrosis is 1-5% and this is one of the most common antenatally detected ultrasound anomalies. [1][2][3][4] Though majority of the cases of antenatally detected hydronephrosis resolves spontaneously, some may be a marker of serious underlying urinary tract abnormalities such as pelviureteric junction obstruction (PUJO), vesicoureteralreflux (VUR), urethral obstruction, megaureters, posterior urethral valve etc. Hence strict postnatal followup becomes a necessity to prevent the subsequent morbidity and mortality due to chronic kidney diseases.…”
Section: Introductionmentioning
confidence: 99%